Systematic Moiety Variations of Ultrashort Peptides Produce Profound Effects on Self-Assembly, Nanostructure Formation, Hydrogelation, and Phase Transition. Issue 1 (December 2017) - Chan, Kiat; Xue, Bo; Robinson, Robert; Hauser, Charlotte
Abstract Self-assembly of small biomolecules is a prevalent phenomenon that is increasingly being recognised to hold the key to building complex structures from simple monomeric units. Small peptides, in particular ultrashort peptides containing up to seven amino acids, for which our laboratory has found many biomedical applications, exhibit immense potential in this regard. For next-generation applications, more intricate control is required over the self-assembly processes. We seek to find out how subtle moiety variation of peptides can affect self-assembly and nanostructure formation. To this end, we have selected a library of 54 tripeptides, derived from systematic moiety variations from seven tripeptides. Our study reveals that subtle structural changes in the tripeptides can exert profound effects on self-assembly, nanostructure formation, hydrogelation, and even phase transition of peptide nanostructures. By comparing the X-ray crystal structures of two tripeptides, acetylated leucine-leucine-glutamic acid (Ac-LLE) and acetylated tyrosine-leucine-aspartic acid (Ac-YLD), we obtained valuable insights into the structural factors that can influence the formation of supramolecular peptide structures. We believe that our results have major implications on the understanding of the factors that affect peptide self-assembly. In addition, our findings can potentially assist current computational efforts to predict and design self-assembling peptide systems for diverse biomedical applications.